2019
DOI: 10.1186/s43014-019-0011-6
|View full text |Cite
|
Sign up to set email alerts
|

Development of milk powder containing Lactobacillus plantarum NCIMB 8826 immobilized with prebiotic hi-maize starch and survival under simulated gastric and intestinal conditions

Abstract: The objectives of this study were to develop a probiotic milk powder containing Lactobacillus plantarum NCIMB 8826 immobilized with prebiotic Hi-maize starch and to analyze cell viability after spray drying and exposure to simulated gastric and intestinal conditions. Milk powders containing free L. plantarum and cells immobilized with Hi-maize starch were assessed. Powders were evaluated during storage at 4°C for 15 days. After spray drying, at 0 and 15 days of storage both treatments had over 8 log CFU/g of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…44 Additionally, the unfavorable higher storage temperatures also interrupt the growth of the cells. Bradford et al (2019) 43 also showed that after a storage period of 15 days at 4 °C, the viable count of probiotic Lactobacillus plantarum NCIMB decreased to <10 7 CFU mL −1 in milk powders, when the reconstituted mixture was subjected to the intestinal fluid for 120 min. In comparison, our samples showed better tolerance and survivability to simulated bile juices even at higher storage temperatures, owing to the potential of legume-based matrices as novel synbiotic components.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…44 Additionally, the unfavorable higher storage temperatures also interrupt the growth of the cells. Bradford et al (2019) 43 also showed that after a storage period of 15 days at 4 °C, the viable count of probiotic Lactobacillus plantarum NCIMB decreased to <10 7 CFU mL −1 in milk powders, when the reconstituted mixture was subjected to the intestinal fluid for 120 min. In comparison, our samples showed better tolerance and survivability to simulated bile juices even at higher storage temperatures, owing to the potential of legume-based matrices as novel synbiotic components.…”
Section: Resultsmentioning
confidence: 99%
“…The reason could be extremely low pH in gastric fluid together with the higher storage temperatures (30 and 35 °C) that can prove to be very distressful for probiotics when passing through it. Bradford et al (2019) 43 reported that after exposure of the probiotic milk powders to simulated gastric fluid for up to 120 min in SGF, they showed a survival count of more than 8 log CFU g −1 on the 15th day of refrigerated storage. Considering this, the survivability of our sample was also >8 log CFU mL −1 even after 15 days of storage at all three temperatures indicating the ability of the legume-based matrix as a potential probiotic carrier.…”
Section: Resultsmentioning
confidence: 99%
“…Various immobilization supports have been explored, with a particular preference for biopolymers and natural supports that meet food-grade standards [26]. One study reported the use of significant quantities of corn starch for the immobilization of probiotics [27]. Calumba et al [19] conducted research with the objective of producing probiotic ale beer, and in their study, they utilized durian powder as a means to support the immobilization of probiotic bacteria in the beer.…”
Section: Brem Bali Innovation and Industrializationmentioning
confidence: 99%
“…Viability of L. acidophilus cells was improved by 70%, 59%, and 6% as a result of using whey protein concentrate, skim milk powder, and sodium caseinate, respectively. Lactobacillus plantarum NCIMB 8826 cells immobilized with hi‐maize starch remained more viable in powdered milk, compared to free cells, after 15 days of storage and during simulated gastric and intestinal transit (Bradford et al., 2019).…”
Section: Application Of Probiotics In Dairy Productsmentioning
confidence: 99%